2012
DOI: 10.1038/ncomms1769
|View full text |Cite
|
Sign up to set email alerts
|

BCR-signalling synergizes with TLR-signalling for induction of AID and immunoglobulin class-switching through the non-canonical NF-κB pathway

Abstract: By diversifying antibody biological effector functions, class switch DNA recombination has a central role in the maturation of the antibody response. Here we show that BCR-signalling synergizes with Toll-like receptor (TLR) signalling to induce class switch DNA recombination. BCR-signalling activates the non-canonical NF-κB pathway and enhances the TLR-dependent canonical NF-κB pathway, thereby inducing activation-induced cytidine deaminase (AID), which is critical for class switch DNA recombination. Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
251
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(267 citation statements)
references
References 58 publications
15
251
0
1
Order By: Relevance
“…However, whether HMGB1 plays a role in autoantibody produc- (14)(15)(16). BCR could enhance the TLR-dependent canonical NF-kB pathway, likely through TRAF6 activation, and TLR could enhance the BCR-activated noncanonical NF-kB pathway by inducing p100 expression, thereby synergizing to cause activation-induced cytidine deaminase and class-switch DNA recombination (56). Meanwhile, HMGB1, which is a component of circulating DNA-containing ICs, could activate the TLR2/ MyD88/miR-155 pathway and, thus, decrease Ets-1 expression, which contributes to plasmacytic differentiation by upregulating the activity of Blimp-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether HMGB1 plays a role in autoantibody produc- (14)(15)(16). BCR could enhance the TLR-dependent canonical NF-kB pathway, likely through TRAF6 activation, and TLR could enhance the BCR-activated noncanonical NF-kB pathway by inducing p100 expression, thereby synergizing to cause activation-induced cytidine deaminase and class-switch DNA recombination (56). Meanwhile, HMGB1, which is a component of circulating DNA-containing ICs, could activate the TLR2/ MyD88/miR-155 pathway and, thus, decrease Ets-1 expression, which contributes to plasmacytic differentiation by upregulating the activity of Blimp-1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that DNA-containing ICs could induce the activation and proliferation of autoreactive B cells through BCR and TLR9 (14)(15)(16). A recent study showed that BCR signaling activated the noncanonical NF-kB pathway and enhanced the TLR-dependent canonical NF-kB pathway, resulting in activation-induced cytidine deaminase, which is critical for class-switch DNA recombination (56). In this study, we demonstrated that HMGB1, which is a component of circulating DNA-containing ICs, could activate the TLR2/MyD88/miR-155 pathway and, thus, decrease Ets-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Quite fittingly, the work of Pone et al has identified an interplay between BCR and TLR signaling in the control of class-switch recombination in the activated B cells. This was mediated by NF-κB signals downstream of both receptors, which, significantly, depended on PI-3K activity in the case of the BCR (8).…”
Section: Inactivation Of Glycogen Synthase Kinase 3β Is Necessary Formentioning
confidence: 98%
“…Indeed, early experiments addressing the in vitro response of mouse B cells to bacterial lipopolysaccharide (LPS) have suggested cooperation of LPS stimulation and BCR engagement in the proliferative B-cell response under certain conditions (6,7). More recent work has uncovered a synergy between TLR and BCR in the control of class-switch recombination in activated B cells (8), and the role of the BCR in the delivery of DNA-or RNA-associated autoantigens to endosomal TLRs in autoimmunity is well established (9). How B cells integrate signals from the BCR and from coreceptors responding to mitogenic stimuli in the induction of the proliferative response is unclear, however.…”
mentioning
confidence: 99%
“…Engagement of TLR4 by lipopolysaccharide (LPS), for example, has been shown to affect many aspects of B-cell activity, including cell proliferation, Ig-class switch, plasma-cell differentiation and antibody production as well as their antigen-presenting capacity. 11,12 In contrast, limited information is currently available regarding the potential role of TLR4-mediated signaling in early B-cell development. In one report, LPS was shown to exert an inhibitory effect on B lymphopoiesis by promoting myeloid differentiation of hematopoietic progenitors through a Myd88-dependent mechanism.…”
Section: Introductionmentioning
confidence: 99%